2010
DOI: 10.1051/0004-6361/201014026
|View full text |Cite
|
Sign up to set email alerts
|

Water formation on bare grains: When the chemistry on dust impacts interstellar gas

Abstract: Context. Water and O 2 are important gas phase ingredients for cooling dense gas when forming stars. On dust grains, H 2 O is an important constituent of the icy mantle in which a complex chemistry is taking place, as revealed by hot core observations. The formation of water can occur on dust grain surfaces, and can impact gas phase composition. Aims. The formation of molecules such as OH, H 2 O, HO 2 and H 2 O 2 , as well as their deuterated forms and O 2 and O 3 is studied to assess how the chemistry varies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 53 publications
(94 reference statements)
5
100
1
Order By: Relevance
“…Following the usual approach in the literature (e.g. Cazaux et al 2010;Taquet et al 2013b), we assume that for each deuterated species, the binding energy is equal to that of the corresponding undeuterated species. We discuss the binding energies further in Sect.…”
Section: Chemical Modelmentioning
confidence: 99%
“…Following the usual approach in the literature (e.g. Cazaux et al 2010;Taquet et al 2013b), we assume that for each deuterated species, the binding energy is equal to that of the corresponding undeuterated species. We discuss the binding energies further in Sect.…”
Section: Chemical Modelmentioning
confidence: 99%
“…Tielens and Hagen (1982) proposed that interstellar water forms on grain surfaces through three reaction channels: hydrogenation of atomic, molecular oxygen and ozone. Using a Monte Carlo approach, Cuppen and Herbst (2007) and Cazaux et al (2010) showed that the contribution of the different formation channels strongly depends on the local environment in interstellar clouds. They concluded that the atomic oxygen channel is the main route in translucent and diffuse clouds, while the molecular oxygen channel, together with the ozone route, is more efficient in dense cold molecular clouds.…”
Section: Surface Formation Of Methanolmentioning
confidence: 99%
“…In particular, many studies have been focused on thermal desorption Noble et al 2015) and nonthermal processes, such as photo-desorption (DeSimone et al 2013;Bertin et al 2013), sputtering (Johnson et al 2013;Cassidy et al 2013), cosmic ray (CR) desorption (Leger et al 1985;Hasegawa & Herbst 1993;Ivlev et al 2015), and chemical desorption (Cazaux et al 2010;Dulieu et al 2013;.…”
Section: Introductionmentioning
confidence: 99%